Sources, Environmental Levels and Toxicity of Organotin in Marine Environment-A Review - K. Okoro, Hussein; S. Fatoki, Olalekan; A. Adekola, Folahan; J. Ximba, Bhekumusa; G. Snyman, Reinette (Asian Journal of Chemistry, 2010)
Organotin compounds are highly versatile group of organometallic chemicals used in industrial and agricultural applications. The growing use of organotin containing compounds such as agricultural pesticides contaminates the aquatic environment by leaching and runoff. The presence of organotin compounds in environmental samples suggest to the vast increase in the use of organotin made products which affects all facets of the ecosystems and thus lead to the global ban on its application. A lot of work has been done on the presence of organotin compounds in environmental samples. The sources, human health risk and speciation of organotin compounds are discussed in this paper. The use of organotin compounds as biocides in antifouling paints has been the major believe for the sources but a large diversity of this compound can be detected in various environmental samples. The uses of organotin compounds as fungicide, glass coating, catalyst, PVC thermo stabilizer are the important sources of these contaminants. The accumulation of organotin compounds in the sea sediment or marine organisms such as fish, shells and squids are the possible ways of exposure to human, if it is consumed. The predominance of parent compounds (tributyltin and triphenyltin) is commonly found and this may indicate their slow degradation in sediment, biota and sea water samples and when recent inputs occur. The detection level of organotin compounds such as methyl butyltin, dibutyltin, tributyltin and triphenyltin are low in developed countries because organotin health risks are under control unlike the developing countries where their use is not controlled. Thus, there is need to monitor organotin contamination from large shipping vessels.